Chemical cues linked to risk: Cues from below‐ground natural enemies enhance plant defences and influence herbivore behaviour and performance. (27th February 2019) - Helms, Anjel M.; Ray, Swayamjit; Matulis, Nina L.; Kuzemchak, Margaret C.; Grisales, William; Tooker, John F.; Ali, Jared G.
Abstract: Chemical cues are essential for many ecological interactions. Previous studies of chemically mediated multitrophic interactions have typically focused on responses to cues from plants or herbivores above‐ground. It is increasingly clear, however, that below‐ground cues and those produced by organisms at higher trophic levels also have ecological importance. Prey animals often avoid predator odours to improve survival, and previous research has documented enhanced plant resistance following contact with below‐ground natural enemies, though the ecological basis was unknown. Here, we investigated plant and insect responses to chemical cues from below‐ground natural enemies and explored the ecological significance of these cues for multitrophic interactions. More specifically, we examined the influence of odours emitted by entomopathogenic nematodes (EPNs), a natural enemy of insect herbivores, on the performance and behaviour of their insect prey and the defence responses of nearby plants. Our findings revealed that EPN‐infected insect cadavers emit a characteristic blend of volatile compounds with bioactivity in plants and insects. EPN chemical cues influenced both performance and preference of a specialist herbivore, Colorado potato beetle (CPB, Leptinotarsa decemlineata ), feeding on its host plant, potato ( Solanum tuberosum ). CPB larvae consumed less leaf tissue and gained less mass feeding on plants exposed to EPN cues compared to control plants. Female CPBs laid fewer eggs on plants with EPN cues than on controls, indicating deterrence by EPN cues or EPN‐altered plant defences. Plant defences were enhanced by exposure to live EPNs or EPN chemical cues. Potato plants exposed to EPN infective juveniles induced higher amounts of the defence hormone salicylic acid (SA) and had higher expression of the pathogenisis‐related gene PR‐1(PR4) in foliar tissue. Exposing plants to EPN cues primed induction of SA and jasmonic acid in response to feeding damage by CPB larvae. These findings suggest that herbivores avoid cues from their EPN natural enemies and plants respond to the beneficial nematodes by enhancing systemic defences that reduce herbivore performance. This work has important implications for the chemical ecology of tritrophic interactions as we report that the third trophic level can play direct and indirect roles in plant defence. Aplain language summary is available for this article. Abstract : Plain Language Summary